Las Normas Antielusivas Específicas de la Ley Interna y su Aplicación a Nivel del Tratado - Villanueva Gutiérrez, Walker (2014)
In this article, the author analyzes if the application of the Specific Antievasive Rules (NAE) is compatible in the scope of the Convention for the Avoidance of Double Taxation (CDI). For this purpose, he investigates if the Peruvian legal system adopts a monistic or dualistic position on the incorporation of CDI’s, so that the relationship between internal law and treaty by the technique of remission is established.